Some calculations for 12C in the α-particle model - Aguilera-Navarro, V.C; Portilho, O (Elsevier, 1977)
In the representation of the 12C nucleus as three finite structureless α particles interacting through phenomenological potentials, we calculate the lower 0+ and 2+ energy levels, elastic and inelastic charge form factor, and transition widths. We use a variational method taking as a trial function a linear combination of harmonic-oscillator eigenfunctions in an approximation of 10 quanta. © 1977.